Aerobic training with blood flow restriction for endurance athletes: potential benefits and considerations of implementation - Smith, N. D. W.; Scott, B. R.; Girard, O.; Peiffer, J. J. (The Journal of Strength and Conditioning Research, 2022)
Low-intensity aerobic training with blood flow restriction (BFR) can improve maximal oxygen uptake, delay the onset of blood lactate accumulation, and may provide marginal benefits to economy of motion in untrained individuals. Such a training modality could also improve these physiological attributes in well-trained athletes. Indeed, aerobic BFR training could be beneficial for those recovering from injury, those who have limited time for training a specific physiological capacity, or as an adjunct training stimulus to provide variation in a program. However, similarly to endurance training without BFR, using aerobic BFR training to elicit physiological adaptations in endurance athletes will require additional considerations compared with nonendurance athletes. The objective of this narrative review is to discuss the acute and chronic aspects of aerobic BFR exercise for well-trained endurance athletes and highlight considerations for its effective implementation. This review first highlights key physiological capacities of endurance performance. The acute and chronic responses to aerobic BFR exercise and their impact on performance are then discussed. Finally, considerations for prescribing and monitoring aerobic BFR exercise in trained endurance populations are addressed to challenge current views on how BFR exercise is implemented.